Improvement Strategy of Seaweed Farmer Community for Increasing Capabilities in the Dry-seaweed Supply Chain in Takalar District, Indonesia - Imran Muhtar; Andi Ridwan Makkulawu (International Journal of Education, Vocational and Social Science, 2023)
The common problems of seaweed farmers are caused by low human capital, farmer's performance and supply chain capabilities, resulting in a low bargaining position in the dry-seaweed farmer's supply chain business. This study aims to identify and formulate strategies to increase farmer capabilities in the supply chain from the perspective of human capital, farmer's performance and supply chain management using a fish-bone and AHP approach. The research was conducted by direct observation and interviews with respondents from stakeholders. The research results show that most influencing factor is the supply chain managemen (70.5%) with the most influencing sub factor, post-harvest (63.7%). The second order factor is human capital (21,9%) with the dominant sub-factor is skills (44%). The third order factor is farmer's performance (7.46%) with the dominant sub-factor is process innovation (29.8%). The results of the respondents' decisions on alternative solutions to farmers' capabilities in the supply chain are: Improvement Training Program (46.3%), Implementation of Policies and Programs (26.6%), Improving Farmer's Competence and Management (16,6%), and Changing the Farmer's Work-Ethic (10,5%). These results can be used as a reference for government policies in public decision making.